Studying of immunophysiological properties of Yersinia Pestis strains with various plasmid composition - V. I. Dubrovina; G. B. Mukhturgin; S. V. Balakhonov; S. A. Vityazeva; T. P. Starovoytova; T. A. Ivanova; Z. A. Konovalova; A. M. Vladimirova (Acta Biomedica Scientifica, 2013)
Data of Yersinia pestis plasmid structure influence on its adhesive properties and phagocytic activity of peritoneal macrophages in vitro are represented. It is shown that Y. pestis strains of diverse subspecies differing by a plasmid profile, particularly by one of the plasmids (pYP, pYV) lacking, possess low adhesive activity and promote the increase of laboratory animal phagocyte absorbing capacity.